Rebranding Universitas Karya Husada Semarang Sebagai Upaya Peningkatan Brand Awarness - Risma Fitriani; Aris Sarwo Nugroho; Irdha Yunianto (UNIVERSITAS STEKOM, 2025)
This study explores the rebranding of Universitas Karya Husada Semarang as a strategic effort to enhance brand awareness in a competitive higher education environment. The research adopts a qualitative descriptive approach combined with the Research and Development (R&D) method to design and validate an effective rebranding strategy. Data were collected through observations, interviews with university stakeholders, and questionnaires distributed to students and the general public. The rebranding process involves updating the visual identity, refining brand communication, and strengthening institutional positioning. The R&D stages include problem identification, data collection, product design, expert validation, and limited testing. Results show that a structured, research-based rebranding approach significantly improves brand awareness and public perception. This initiative not only reinforces the university’s image but also increases its appeal to prospective students. The study offers strategic insights for other educational institutions seeking to strengthen their brand identity.